Proposal of a user-centred approach for CPS design: pillbox case study. Issue 34 (2019) - Merlo, C.; Akle, A. Abi; Llaria, A.; Terrasson, G.; Villeneuve, E.; Pilnière, V.
Abstract: Product design greatly evolves for years, due to the increasing complexity of products, from simple monodisciplinary products to mechatronics systems then cyber-physical systems. Teams involved in the development of such systems are strongly interdisciplinary and require adequate engineering design methods. We propose hereafter a dedicated design process that integrates systems engineering approach, creativity tools and user-centered design methods. This design process has been implemented within a case study from e-health sector: a home-care provider asked us for developing and experimenting a 'connected' pillbox. After detailing main results of this development, we analyze them and propose methodological improvements. We finally conclude on some perspectives for studying engineering design in the context of global e-health systems.